2018
DOI: 10.12693/aphyspola.134.998
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Ga-Doped Magnetite Nanoparticles

Abstract: This paper reports our progress toward developing the best methods to prepare Ga-doped magnetite nanoparticles. Results of X-ray powder diffraction, small angle neutron scattering and the Mössbauer spectroscopy measurements of core-shell Ga0.2Fe2.8O4/ Fe3O4 and Fe3O4/Ga0.2Fe2.8O4 nanoparticles are presented. They all were found to crystallize in the cubic structure. The diffraction data confirmed high sensitivity of the phase homogeneity depending on the preparation method. The volume of the unit cell has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 12 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…The presence of gallium in the activated catalyst suggests that dopant incorporation can occur during the activation procedure since no evidence of gallium incorporation was found in the catalyst precursor. Earlier, Kohout et al and Rećko et al suggested preferential occupation of tetrahedral sites of magnetite by gallium using NMR and Mössbauer spectroscopy, respectively, whereas a study by Wang et al indicated incorporation of gallium into both tetrahedral and octahedral sites using Mössbauer spectroscopy. These inconclusive findings might be due to the fact that the samples were prepared in different ways.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of gallium in the activated catalyst suggests that dopant incorporation can occur during the activation procedure since no evidence of gallium incorporation was found in the catalyst precursor. Earlier, Kohout et al and Rećko et al suggested preferential occupation of tetrahedral sites of magnetite by gallium using NMR and Mössbauer spectroscopy, respectively, whereas a study by Wang et al indicated incorporation of gallium into both tetrahedral and octahedral sites using Mössbauer spectroscopy. These inconclusive findings might be due to the fact that the samples were prepared in different ways.…”
Section: Resultsmentioning
confidence: 99%
“…Magnetites doped with bi- and trivalent cations form a group of innovative materials [ 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Among these, gallium nanoferrites seem to be promising candidates for use in magnetic hyperthermia [ 12 ].…”
Section: Introductionmentioning
confidence: 99%